2015
DOI: 10.1186/s12882-015-0151-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of hearing impairment with chronic kidney disease: a cross-sectional study of the Korean general population

Abstract: Background: We aimed to evaluate the association between hearing impairment and the prevalence of chronic kidney disease (CKD) in the largest population-based cross-sectional study to date. Methods: This cross-sectional study was based on the Korean National Health and Nutritional Examination Survey (KNHANES). It included 5226 participants ≥19 years of age whose estimated glomerular filtration rate (eGFR) and hearing threshold had been measured. We diagnosed CKD as an eGFR <60 mL/min/1.73 m

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 16 publications
9
32
0
1
Order By: Relevance
“…The association between kidney function decline and hearing loss found in our study was consistent with some previously published studies [23,24]. Seo et al [24] found that an eGFR < 60 mL/min/1.73 m 2 had a significant independent influence on the hearing status of adults, and they reported that the OR of hearing impairment in participants with eGFR < 60 mL/min/1.73 m 2 was 1.25…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The association between kidney function decline and hearing loss found in our study was consistent with some previously published studies [23,24]. Seo et al [24] found that an eGFR < 60 mL/min/1.73 m 2 had a significant independent influence on the hearing status of adults, and they reported that the OR of hearing impairment in participants with eGFR < 60 mL/min/1.73 m 2 was 1.25…”
Section: Discussionsupporting
confidence: 92%
“…It is a little bit difficult to compare the prevalence of hearing loss in this study with previous studies due to the fact that the included participants in different studies were in different age groups, and the hearing loss was defined and measured using different instruments in different studies. The pure-tone audiometry and self-reporting are two common ways to assess hearing status in hearing related studies [23,24,[29][30][31][32][33][34]. Pure tone audiometry is to find the hearing threshold at a specific frequency [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study we have performed a correlation study between eGFR and PTA parameters and our result were comparable to Seo et al, who found that the correlation between eGFR and mean thresholds at low, mid, and high frequency ranges had meaningful negative correlations with eGFR values. 22 We performed a stage wise distribution of CKD patients according to their severity, and we found that for low frequency range in stage 2 and 3 patients, maximum hearing loss was of mild to moderate degree in nature, whereas in stage 4 and 5, maximum hearing loss was also mild to moderate in nature. Although severe to profound hearing loss was also more in stage 4 and 5 patients as compared to stage 2 and 3.…”
Section: Discussionmentioning
confidence: 93%